KESUNGGUHAN MENURUT KOLOSE 3:23-24A DALAM PELAYANAN MEMIMPIN PUJIAN DAN PENYEMBAHAN DI IBADAH KAUM MUDA GEREJA BETH-EL TABERNAKEL JEMAAT GUNUNGAN MOJOKERTO JAWA TIMUR - Muri, Ance (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2025)
Abstract: Praise and worship are very important in devotion. The praise and worship leader is tasked and responsible for bringing the congregation to enjoy God's presence and the joy of praising and worshiping God. This requires sincerity in leading praise and worship. The problem that causes praise and worship leaders to be less than optimal in worship is lack of training before starting worship. This research aimed to examine the seriousness according to Colossians 3:23-24a in leading praise and worship at the youth services of Beth-El Tabernacle Church, Gunungan Congregation, Mojokerto, East Java, using a combination of quantitative and qualitative research methods. Quantitative research using a sample of 17 people using a questionnaire of 7 questions with an ordinal scale to assess the seriousness according to Colossians 3:23-24 in leading praise and worship at the youth services of the Beth-El Tabernacle Church, Gunungan Congregation, Mojokerto, East Java, which has been tested for validity and reliability. The results of the questionnaire showed an average of often 64.72%, sometimes 32.71% and never 2.57%. Qualitative research used interviews with a sample of 5 people to assess the same Church youth worship leaders' understanding of the meaning of praise and worship and how to lead it with sincerity, as well as what challenges they face. The results of the interview obtained were that the praise and worship leader understood the meaning of praise and worship in accordance with God's Word and the meaning of sincerity in leading praise and worship which was stated to live righteously and have submission and needed good preparation before the service began. However, the challenges faced are lack of preparation because some of their homes are far from the church and sometimes they are appointed suddenly, and there are those who don't understand music and are less able to lead. Conclusion: The average questionnaire results are often 64.72%, sometimes 32.71% and never 2.57%. This is explained by the results of qualitative research where praise and worship leaders actually understand the meaning of leading praise and worship with sincerity, but because of the existing challenges they do not do it optimally. Keywords: Leader, Praise and Worship, Sincerity